Evaluation of Excess Deaths in a Tertiary Hospital in Urban Northern Nigeria during the COVID-19 Pandemic (EDiK-2020 Study) - Galadanci, Hadiza; Abubakar, Isa; Musa, Baba; Adamu, Aishatu; Gadanya, Muktar; Tsiga‑Ahmed, Fatimah; Kwaku, Aminatu; Jalo, Rabiu; Bashir, Usman; Abdullahi, Hadiza; Farouk, Zubaida; Dankishiya, Faisal; et al. (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: The morbidity and mortality arising from the COVID-19 pandemic in low- and middle-income countries were further worsened by the disruption in health systems and diversion of strained health resources for emergency response.Aim:This study ascertained whether there was an increase in the number of deaths recorded in Kano, Nigeria, during the pandemic, compared to the preceding 3 years and identified the potential causes of these deaths.Materials and Methods: Using a retrospective design, data were collected from a tertiary hospital in Kano from January to June 2020. Data on number and date of deaths, as well as clinical information of the deceased, were retrieved from hospital records. Comparison data were collected on all deaths and admissions in the hospital within a similar period (January–June) of 2017–2019.Results: The age of the deceased ranged from one day to 115 years, with the majority being males (n = 414; 63.2%) and adults (n = 491; 75.0%). The majority did not have history of recent travel (n = 570; 87.0%), contact with COVID-19 suspected cases (n = 622; 95.0%), or confirmed COVID-19 (n = 625; 95.4%). Slightly less than half (n = 262; 46.2%) died within 24h of admission. The majority (n = 452; 79.7%) died within 7 days of admission. The most common cause of death recorded on admission was sepsis (n = 66; 10.1%), while 53 (8.1%) were brought in dead. SARS-CoV-2 infection was the documented cause of death in twelve patients (1.8%). More than half (n = 378; 57.7%) had underlying medical conditions, of which hypertension (n = 172; 45.5%) was the most common. The highest annual average deaths (178) and admissions (2179) were recorded in 2019, while 135 deaths and 1532 admissions were recorded in 2020. Most deaths occurred in April 2020 (208), while the highest number of admissions was recorded in March 2020. Mortality was higher in April of 2020 (14.1%, 95% CI: 12.4%–16.0%) compared to the same month in 2017 (7.6%, 95% CI: 5.9%–9.7%), 2018 (8.4%, 95% CI 7.0%–10.2%), and 2019 (8.5%, 95% CI 7.3–9.8%).Conclusion: In summary, we found excess mortality rates during the COVID-19 pandemic in Kano, Nigeria, consistent with prior studies.